2021
DOI: 10.3390/life11101085
|View full text |Cite
|
Sign up to set email alerts
|

Modified VMAT Plans for Locally Advanced Centrally Located Non-Small Cell Lung Cancer (NSCLC)

Abstract: Objectives: This study aimed to find the optimal radiotherapy VMAT plans, that achieved high conformity and homogeneity to the planned target volume (PTV), and minimize the dose to nearby organs at risk including the non-PTV lung, heart and oesophagus for patients with centrally located non-small Cell Lung Cancer. Methods: A total of 18 patients who were treated for stage III centrally located non-small Cell Lung Cancer were selected retrospectively for this study. Identical CT datasets, 4D CT and structure da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Volumetric modulated arc therapy (VMAT) facilitates the conformal dose delivery to the PTV by variation in dose rate and field size aperture with a gantry that rotates at varied speeds. It has been applied for treating prostate cancer [6,7] and liver cancer [8,9] in coplanar VMAT and lung cancer in non-coplanar VMAT [10]. In view of cranial regions, previous studies suggested that non-coplanar VMAT demonstrated a dose reduction to organs at risk (OARs) located in the peripheral regions, including the hippocampus [11][12][13], normal brain tissue, the temporal lobe and the cochlea [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric modulated arc therapy (VMAT) facilitates the conformal dose delivery to the PTV by variation in dose rate and field size aperture with a gantry that rotates at varied speeds. It has been applied for treating prostate cancer [6,7] and liver cancer [8,9] in coplanar VMAT and lung cancer in non-coplanar VMAT [10]. In view of cranial regions, previous studies suggested that non-coplanar VMAT demonstrated a dose reduction to organs at risk (OARs) located in the peripheral regions, including the hippocampus [11][12][13], normal brain tissue, the temporal lobe and the cochlea [14,15].…”
Section: Introductionmentioning
confidence: 99%